Comparative analyses of nutritional effectiveness of food subsidies and other food-related interventions - Kennedy, Eileen T.; Alderman, Harold (International Food Policy Research Institute, 1987)
Malnutrition affects millions of people in developing countries; it affects preschool-aged children and pregnant and lactating women acutely. In the long run, most policymakers would agree that the elimination of poverty is the most effective way of dealing with protein-calorie malnutrition. In the short run, however, governments and international institutions have pursued a variety of intervention strategies in the hope of alleviating malnutrition.